Mapping ENU-induced thymic lymphoma susceptibility loci in C57BL/6 mice - Romao, P.L. (2017)
Tumour development is a complex process involving susceptibility loci (oncogenes) and the accumulation of spontaneous somatic mutations in tumour suppressor genes that interact to result in cancer. Tumours may require the accumulation of a variety of mutations before developing but the general principle is that the mutations result in an imbalance between the oncogene and tumour suppressor gene function (Berger et al., 2011). This multi-hit process can be tested by subjecting strains of mice susceptible to certain types of tumours to chemical mutagens, thereby inducing further mutations. This technique is used in this study to identify loci resulting in the susceptibility to thymic lymphoma in the C57BL/6J strain in order to further our understanding of the processes involved in the development of such tumours.